2015
DOI: 10.3354/meps11176
|View full text |Cite
|
Sign up to set email alerts
|

Fine-scale whisker growth measurements can reveal temporal foraging patterns from stable isotope signatures

Abstract: Stable isotope analysis of slow-growing, metabolically inert tissues is a common method for investigating foraging ecology in migratory animals, as direct observations of feeding are often not possible. Using tissue growth dynamics to interpret foraging timelines can maximize the utility of foraging data; however, applying inappropriate growth models is problematic, and high-resolution growth measurements are seldom made. We used photogrammetry to repeatedly measure the length of whiskers in 93 follicles over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
76
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(86 citation statements)
references
References 46 publications
9
76
1
Order By: Relevance
“…The ability to obtain fine-scale, temporal integrated biogeochemical data was demonstrated in a similar study conducted on a single, captive adult female northern elephant seal, Mirounga angustirostris (Beltran et al 2015). However, ascertaining the starting date of the vibrissal growth remains a prerequisite to assign dates to dietary data (Greaves et al 2004).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The ability to obtain fine-scale, temporal integrated biogeochemical data was demonstrated in a similar study conducted on a single, captive adult female northern elephant seal, Mirounga angustirostris (Beltran et al 2015). However, ascertaining the starting date of the vibrissal growth remains a prerequisite to assign dates to dietary data (Greaves et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The vibrissae of otariids, such as Antarctic fur seals Arctocephalus gazella (Walters 2014), and Steller sea lions Eumetopias jubatus (Hirons et al 2001), grow linearly and are retained for multiple years (Hirons et al 2001;Cherel et al 2009;Kernaléguen et al 2012). In contrast, the vibrissae of phocids, such as grey seals Halichoerus grypus, and P. vitulina, grow asymptotically and are characterised by an asynchronous growth and replacement pattern (Greaves et al 2004;Hall-Aspland et al 2005;Beltran et al 2015). Furthermore, it is suggested that vibrissae of phocids have short retention times; for example, P. vitulina and spotted seals, Phoca largha, shed their vibrissae on an annual basis (Zhao & Schell 2004;McHuron et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations